Struktur Komunitas Mangrove Pesisir Pantai Desa Dalapuli Barat, Bolaang Mongondow Utara - Nurul Auliyah; Agus Blongkod (Universitas Gorontalo, 2018)
Mangrove is one of vegetation on coastal where very important. The aim of research is to know the structure of community of mangrove forests in Dalapuli Barat Village Pinogaluman Sub-district, Bolaang Mongondow Utara District. The method to take the sample in this research is transek square method. The first sample plot is on the left of the path axis and the second sample plot is on the right of the path axis and then alternates. Sampling growth of 2 m x 2 m for the seedling phase, ie regeneration of trees that begin to increase until the power <1.5 m. Example plots are 5 m x 5 m for the stake, ie high regeneration> 1.5 m up to <10 cm in diameter, and. The sample plot is 10 m x 10m for the tree phase, ie trees having a diameter of more than 10 cm. The results of this study are: 8 species of mangrove species are found in Rhyzopora apiculata, Xylocarpus granatum, Cheriops tag, Sonneratia alba, Nypa fruticans, Lumnitzera littorea, pandanus techtorius, and Acanthus ebracteatus The essential tree index value (INP) is 302, Pancang is 302, (scale 0 - 300 and seedling level includes 313. Index diversity of analysis result is low.Â Keywords : Mangrove, Community, Dalapuli Village